Modular multilevel converter: A comparison of pulse-width modulation and current control techniques - Rodrigues, Nuno (2022)
With the constant increase of power converters in industry, the study and comparison of control techniques for these converters are of paramount importance to optimize their functioning, as well as to improve their efficiency. This paper presents a comparison of the most relevant digital control techniques of pulse-width modulation and current control for a modular multilevel converter (MMC), which is a power converter that is increasing in popularity among researchers, and with a steady growth in its literature. Beginning with a theoretical presentation of each control technique and using explanatory figures and computational results, the focus of this paper is the understanding of the modulation and control techniques for the MMC. Since the MMC has a modular structure, the power is distributed among the different submodules, which increases the complexity of the control system. Furthermore, a balancing strategy for the voltage across the capacitor of each submodule of the MMC is also presented. Along with the paper, computer simulations are presented, which were carried out to validate the functioning of the MMC and the control techniques, as well as to understand the differences in the obtained results.